Schrodinger's cat meets Einstein's twins: A superposition of different clock times - Vedral, V; Morikoshi, F (2008)
The phenomenon of quantum superposition, which allows a physical system to exist in different states 'simultaneously', is one of the most bizarre notions in physics. Here we illustrate an even more bizarre example of it: a superposed state of a physical system consisting of both an 'older' version and a 'younger' version of that system. This can be accomplished by exploiting the special relativistic effect of time dilation featuring in Einstein's famous twin paradox. © 2007 Springer Science+Business Media, LLC.